A pragmatic study on the service gap analysis of an Indian public sector bank - Nalini, Rengasamy; Ramachandran, Amudha; Sujatha, Venkatarayareddiar; Radha, Rengaswamy (Business: Theory and Practice, 2014)
Customers are the major stakeholders and their satisfaction forms the basis of the sustainable competitive advantage of the firm. Attracting, satisfying and retaining customers lead to extended customer base and increased profit margins. Thus, the customer satisfaction is the ultimate objective of the firm which is possible by rendering quality service. The State Bank of India (SBI) ranks as 67th in the list of largest banks in the world based on market capitalization as of March 31th 2014. The quality of service extended by the SBI has resulted in customer satisfaction and expanded customer base for the bank. Random sampling method is adopted for the collection of data from the respondents. In Tiruchirappalli regional office of State Bank of India, area operations are selected within 10 Kilometer radius from the Main branch and 60 questionnaires per branch have been distributed in 10 branches. Out of 600 questionnaires, 109 are found incomplete and 491 are fully complete with 81.83% of response rate. The data collected were analysed with the help of MS Excel to identify the gaps. The Cronbach alpha, a measure of internal consistency obtained is 0.925 which is considered to be excellent. This study aims to identify the gaps in the dimensions of service quality by administering SERVQUAL model among the customers in State Bank of India. An overall weighted SERVQUAL score of –1.42866 was arrived, representing a significant inconsistency in meeting customer expectations across all service dimensions. Highest gap scores for reliability and empathy depicts that there is a need for courtesy and politeness among SBI employees which in turn will help to establish a long term relationship with the customers. The relatively low gap scores were found for responsiveness, tangibles and assurance dimensions. The State Bank of India has to take steps to close the gaps and it can be closed by establishing and implementing a service quality information system.